2019
DOI: 10.3892/ol.2019.11100
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis to screen key genes in papillary thyroid carcinoma

Abstract: Papillary thyroid carcinoma (PTC) is the most common type of thyroid carcinoma, and its incidence has been on the increase in recent years. However, the molecular mechanism of PTC is unclear and misdiagnosis remains a major issue. Therefore, the present study aimed to investigate this mechanism, and to identify key prognostic biomarkers. Integrated analysis was used to explore differentially expressed genes (DEGs) between PTC and healthy thyroid tissue. To investigate the functions and pathways associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The analysis of 500 PTC tumors, based on next-generation sequencing, under the genotyping project Cancer Genome Research Network, confirmed four major molecular events present in the majority of PTC cases: BRAF V600E , RAS, and TERT point mutations as well as RET/PTC rearrangements [4]. Although the PTC transcriptome is well characterized [3,[6][7][8] and correlates with some prognostic and genotypic factors [3,4], biological mechanisms of neoplastic transformation in PTC are not unequivocally elucidated. Nevertheless, these data do not explain the whole biology of PTC tumorigenesis and are only to some extent helpful in diagnostics (BRAF, TERT, RET/PTC rearrangements) [9][10][11][12][13][14] and prognosis (BRAF, TERT) [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of 500 PTC tumors, based on next-generation sequencing, under the genotyping project Cancer Genome Research Network, confirmed four major molecular events present in the majority of PTC cases: BRAF V600E , RAS, and TERT point mutations as well as RET/PTC rearrangements [4]. Although the PTC transcriptome is well characterized [3,[6][7][8] and correlates with some prognostic and genotypic factors [3,4], biological mechanisms of neoplastic transformation in PTC are not unequivocally elucidated. Nevertheless, these data do not explain the whole biology of PTC tumorigenesis and are only to some extent helpful in diagnostics (BRAF, TERT, RET/PTC rearrangements) [9][10][11][12][13][14] and prognosis (BRAF, TERT) [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A case-control study reported that a TPO variant is associated with thyroid carcinoma (13). Our previous study and other integrated analyses demonstrated that TPO was significantly downregulated in PTC (10,14). Pathologically, immunohistochemical staining verified that TPO can distinguish PTC from benign thyroid lesions (15).…”
Section: Introductionmentioning
confidence: 88%
“…However, the etiology and molecular biology of PTC remain clear. Previously, we found that both thyroid peroxidase (TPO) and aldehyde oxidase 1 (AOX1) were downregulated in PTC (10,11). However, further experimental verification and studies of the clinical importance of TPO and AOX1 in PTC must be conducted.…”
Section: Introductionmentioning
confidence: 98%
“…In TCGA dataset, ‘01’ representeda primary solid tumor, and ‘11’ represented paracancerous tissue. The Gene Expression Omnibus (GEO) datasets GSE3678 ( ) ( 21 ) and GSE3467 ( ) ( 22 ) were also used for ANGPTL1 expression analysis. The data from TCGA dataset were divided into high (n=250) and low (n=251) ANGPTL1 expression groups based on the median values of ANGPTL1 RNA-seq quantification results and further analyzed using GSEA.…”
Section: Methodsmentioning
confidence: 99%